Fragmentation of natural orbital occupation numbers‐based diagnostic of differential multireference character in complexes with hydrogen bonds. Issue 7 (15th December 2020) - Šulka, Martin; Dubecký, Matúš
Abstract: We explore the possible route to approximate natural orbital occupation numbers‐based diagnostic of differential multireference character of noncovalent energy differences by techniques based on many‐body expansion. It turns out that two‐body fragmentation of monomers may lead to a reasonable approximation of such a diagnostic in hydrogen‐bonded complexes. The results are useful, for example, for assessment of the expected bias cancellation in energy differences of larger systems obtained by single‐reference methods. Abstract : Differential multireference character diagnostic δ can be decomposed by techniques based on many‐body expansion. Two‐body fragmentation may lead to a reasonable approximation of such a diagnostic in hydrogen‐bonded complexes.